2003
DOI: 10.1121/1.4781127
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of a 63 element 1.75-dimensional ultrasound phased array for treating benign prostatic hyperplasia

Abstract: Focused ultrasound surgery (FUS) is a clinical method for treating benign prostatic hyperplasia (BPH) in which tissue is noninvasively necrosed by elevating the temperature at the focal point above 60<th>°C using short sonications. With 1.75-dimensional (1.75-D) arrays, the power and phase to the individual elements can be controlled electronically for focusing and steering. This research describes the design, construction and evaluation of a 1.75-D ultrasound phased array to be used in the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This choice of element dimensions means that Grating lobes will be generated at unwanted locations. It has been found that a value of Grating lobe that is 20% of the maximum intensity is acceptable as it will not lead to temperatures above 41°C at the location of the Grating lobes, unless excessive acoustical power is used [8][9][10].…”
Section: Grating Lobesmentioning
confidence: 98%
See 1 more Smart Citation
“…This choice of element dimensions means that Grating lobes will be generated at unwanted locations. It has been found that a value of Grating lobe that is 20% of the maximum intensity is acceptable as it will not lead to temperatures above 41°C at the location of the Grating lobes, unless excessive acoustical power is used [8][9][10].…”
Section: Grating Lobesmentioning
confidence: 98%
“…Previous effective flat arrays that were able to generate lesions in parts of the prostate include a two-dimensional (2-D) 8 9 8 phased array that was capable of electrically focusing and steering the ultrasound beam over a portion (less than half) of the prostate [8]. Another example is a 1.75-dimensional (1.75-D) 21 9 3 phased array that had the capability of focusing and steering the ultrasound beam at three different parallel planes inside the prostate [9,10]. Other flat shapes that were introduced in the past were 1.5-dimensional (1.5-D) 64 9 4 and 42 9 3 phased arrays that were used to perform tissue ablation on cancerous cells in the prostate [2].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to a full matrix array (195 elements), a sparse array (64 active elements) has a benefit from the reduced number of elements. Additionally, an array with tapered elements was designed to significantly suppress grating lobes (Benkeser et al 1987;Saleh and Smith 2005). According to the simulation results, the sparse array model with tapered elements produced no significant grating lobes.…”
Section: Sparse Phased Arraymentioning
confidence: 99%
“…Both USG-guided probes and MRI-guided systems have been developed. The USG probes are inserted per rectum and incorporate both imaging and therapeutic transducers in one unit, [35][36][37][38][39][40][41] such as Ablatherm (Edap Technomed, France) and the Sonablate (Focus Surgery Inc, US), whereas a prostate-dedicated MRI-HIFU system makes use of either the transrectal (ExAblate OR; InSightec) or transurethral (Philips Healthcare) approach.…”
Section: Transrectal Devicesmentioning
confidence: 99%